Growth Response Of Cavendish Banana Planlets cv. grand naine At The Acclimatization Phase With Different Doses Of Foliar Fertilizer And Vitamin B1 - Rahayu, Puspita Sri; Susiyanti, Susiyanti; Isminingsih, Sulastri; Utama, Putra (Jurnal Agroekoteknologi, 2023)
This research aimed to determine the effect of foliar fertilizer and vitamin B1 on the growth of cavendish banana plantlets at the acclimatization phase. This research was an experimental research conducted from July to October 2023 in the Greenhouse of the Agroecotechnology Department, Faculty of Agriculture, Sultan Ageng Tirtayasa University, Serang, Banten. This research used a Factorial Randomized Block Design (RCBD) which consisted of two factors. The first factor was the foliar fertilizer dosage consist of 5 levels, namely 0 g/l (N0), 1 g/l (N1), 1.5 g/l (N2), 2 g/l (N3) and 2.5 g/l (N3). l (N4). The second factor was the vitamin B1 dosage  which consists of  3 levels, namely 1 ml/l (M1), 1.5 ml/l (M2) and 2 ml/l (M3). Each treatment was repeated three times to obtain 45 experimental units. The results showed that the foliar fertilizer dosage treatment had an effect on the parameters of plant height (2.79 cm), stem diameter (3.03 mm), number of leaves (2.33 leaves), leaf length (1.50 cm), leaf width (0 .90 cm), chlorophyll content (28.08 units). Meanwhile, the vitamin B1 dose treatment affected the parameters of stem diameter (2.20 mm), number of leaves (2 leaves), leaf length (1.44 cm) and leaf width (0.90 cm). There is an interaction between giving a dose of 2 g/l foliar fertilizer and 2 ml/l vitamin B1 on stem diameter  5 WAP (1.57 mm) and number of leaves  6 and 7 WAP (2 and 3 leaves).